Synergistic activity of RSL3 and Pyrimethamine to inhibit the proliferation of Plasmodium falciparum - Nikolova, Vella Georgieva; Linnemannstöns, Karen; Zahoruiko, Anastasiia; Ganter, Markus; Lüder, Carsten G.; Dobbelstein, Matthias (Antimicrobial agents and chemotherapy, 2025)
Malaria tropica, caused by Plasmodium falciparum (P. falciparum), remains a global health challenge with limited therapeutic options. In mammalian cells, the small-molecule compound RAS-selective lethal 3 (RSL3) induces ferroptosis via lipid peroxidation. In this study, we demonstrate that RSL3 synergizes with Pyrimethamine, an inhibitor of P. falciparum dihydrofolate reductase (DHFR), to suppress parasite proliferation in red blood cells (RBCs). A similar synergistic effect was observed with Cycloguanil, a structural analog of Pyrimethamine, but not with other DHFR inhibitors or alternative agents that induce ferroptosis in nucleated mammalian cells. Notably, Ferrostatin-1, an antagonist of lipid peroxidation, largely failed to rescue parasite growth in the presence of RSL3, possibly suggesting a mechanism distinct from canonical ferroptosis. These findings suggest that the synergy may involve unidentified targets of RSL3 and Pyrimethamine in P. falciparum, divergent from those described in mammalian systems. Moreover, RSL3 and related compounds could serve as promising adjuvants to enhance the antimalarial efficacy of Pyrimethamine and potentially overcome drug resistance.
Online veröffentlicht: 18. August 2025
Gesehen am 13.01.2026